2018
DOI: 10.1038/s41598-018-33657-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Nutrient Database in Estimating the Dietary Phosphorus-to-Protein Ratio and Using a Boiling Method in Low-Phosphate Hospital Diets

Abstract: The use of the dietary phosphorus-to-protein ratio (PPR) to reduce dietary phosphorus while maintaining protein intake is valuable for nutritional management in the dialysis population, but the actual PPR values in hospital meals have not been determined. We aimed to determine the accuracy of a nutrient database for estimating the PPR in low-phosphate hospital diets compared with the accuracy of chemical analysis and produce hospital diets with low-phosphate content by boiling meat for 30 minutes before cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…It was noted in one study that energy intake in renal patients on hemodialysis treatment was below recommendations, becoming more severe than low protein intake. 24 It is noteworthy that the evaluation of the quality of the protein ingested is also very relevant, that is, a minimum of 50% of high biological value proteins (HBV) must be prioritized in order to ensure the intake of essential amino acids. In this study, it was observed that the amount of HBV proteins recorded was within the recommended (69%), while 31% of the patients had consumption below the recommended, corroborating the research reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted in one study that energy intake in renal patients on hemodialysis treatment was below recommendations, becoming more severe than low protein intake. 24 It is noteworthy that the evaluation of the quality of the protein ingested is also very relevant, that is, a minimum of 50% of high biological value proteins (HBV) must be prioritized in order to ensure the intake of essential amino acids. In this study, it was observed that the amount of HBV proteins recorded was within the recommended (69%), while 31% of the patients had consumption below the recommended, corroborating the research reported.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was observed that the amount of HBV proteins recorded was within the recommended (69%), while 31% of the patients had consumption below the recommended, corroborating the research reported. 24 It is contextualized that serum albumin had been identified as a predictor of mortality in hemodialysis (HD) patients. It is understood that the normalized protein catabolic rate (nPCR) less than 0.8 or greater than 1.4 g/kg/day was also associated with higher mortality.…”
Section: Resultsmentioning
confidence: 99%
“…One may argue that the baseline diets may have been underestimated by inaccuracies of food composition tables, as has been shown numerous times in the literature (6). However, Tsai et al (7) showed in another recent publication that food composition table estimates of phosphorus content of natural foods, free from phosphate additives, may not be marred by the same underestimation as foods with additives. In fact, their estimates of phosphorus content from food composition tables closely matched the chemically analyzed values (7).…”
mentioning
confidence: 99%
“…However, Tsai et al (7) showed in another recent publication that food composition table estimates of phosphorus content of natural foods, free from phosphate additives, may not be marred by the same underestimation as foods with additives. In fact, their estimates of phosphorus content from food composition tables closely matched the chemically analyzed values (7). Thus, there is no strong reason to suspect the baseline values for phosphorus intake were underestimated drastically in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation